EFFECT OF LEADERSHIP ON EMPLOYEE ENGAGEMENT: HOW TO CREATE HIGH-ENGAGEMENT IN A LOW-ENGAGEMENT WORLD? - Knaapi, Janette (My University, 2015)
When it is a time of change or when the economic situation is turbulent, companies rely on engaged employees. Companies must retain the most engaged employees in order to be successful even in a time of uncertainty. They turn to employees that have an entrepreneurial mindset and who have the will and capability to go the extra mile. A leader can greatly affect his or her subordinates’ engagement level. Therefore, the aim of this research is to understand what is meant by employee engagement and identify the factors and behaviors that lead to higher engagement. A qualitative research design was chosen because of the nature of the research. The qualitative method enabled the researcher to gather rich information about the concept and the leadership behaviors that lead to higher engagement. Seven semi-structured interviews were carried out in Finnish to complete this qualitative case study. The interviews were recorded and the data was fully transcribed. The main findings of this study suggests that employee engagement is its own concept and therefore it should not be mixed with other concepts. Employee engagement arises from the employee and any employee needs to have certain traits while also believing in the company he or she is working for. Although, it is observed that employee engagement is built together between a leader and a subordinate. Employee engagement is like a two-way street and both of the participants need to be involved to build high engagement. It was found that the leader can raise the quality of engagement with certain behaviors. The main leadership behaviors that lead to higher engagement are trust, meaningfulness, challenge, goal setting, rewarding and feedback.
Keywords: Employee Engagement; Leadership; Expert Organization; Knowledge Workers; New World of Work; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|